Co-evolution of Bacterial Ribosomal Protein S15 with Diverse mRNA Regulatory Structures. - Betty L Slinger; Hunter Newman; Younghan Lee; Shermin Pei; Michelle M Meyer (PLoS Genetics)
RNA-protein interactions are critical in many biological processes, yet how such interactions affect the evolution of both partners is still unknown. RNA and protein structures are impacted very differently by mechanisms of genomic change. While most protein families are identifiable at the nucleotide level across large phylogenetic distances, RNA families display far less nucleotide similarity and are often only shared by closely related bacterial species. Ribosomal protein S15 has two RNA binding functions. First, it is a ribosomal protein responsible for organizing the rRNA during ribosome assembly. Second, in many bacterial species S15 also interacts with a structured portion of its own transcript to negatively regulate gene expression. While the first interaction is conserved in most bacteria, the second is not. Four distinct mRNA structures interact with S15 to enable regulation, each of which appears to be independently derived in different groups of bacteria. With the goal of understanding how protein-binding specificity may influence the evolution of such RNA regulatory structures, we examine whether examples of these mRNA structures are able to interact with, and regulate in response to, S15 homologs from organisms containing distinct mRNA structures. We find that despite their shared RNA binding function in the rRNA, S15 homologs have distinct RNA recognition profiles. We present a model to explain the specificity patterns observed, and support this model by with further mutagenesis. After analyzing the patterns of conservation for the S15 protein coding sequences, we also identified amino acid changes that alter the binding specificity of an S15 homolog. In this work we demonstrate that homologous RNA-binding proteins have different specificity profiles, and minor changes to amino acid sequences, or to RNA structural motifs, can have large impacts on RNA-protein recognition.